Balancing Stakeholders’ Interest and Sustainability: Petronas’ Strategic Response to The Global Energy Transition - Febrina, Ilza; Zubir, Siti Mahfuzah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines Petronas' strategic response to the global energy transition, focusing on its adoption of renewable energy, integration of sustainability practices, and the influence of leadership. This study employs qualitative document analysis to assess how Petronas integrates its strategies with Environmental, Social, and Governance (ESG) principles, as well as the United Nations' Sustainable Development Goals (SDGs), while also considering the wide-ranging interests of its stakeholders. The findings highlight Petronas’ investments in green hydrogen, sustainable materials, and digital technologies, emphasizing both decarbonization efforts and long-term value creation for key stakeholders, including governments, investors, employees, and local communities. Moreover, the study underscores the pivotal role of transformational leadership in shaping Petronas' sustainability strategy and its impact on stakeholder relationships. The insights provided have broader implications for other National Oil Companies (NOCs), demonstrating that enhancing sustainability profiles not only strengthens stakeholder relations but also supports long-term profitability through sustainable development.